2016
DOI: 10.1111/inr.12306
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced by international nurses when migrating: an integrative literature review

Abstract: Aim:Results from this literature review were used to identify the challenges faced by international nurses in their host countries following migration. Background: The increasing strain of nursing shortages in the healthcare system has led to the recruitment of international nurses among many countries. However, following migration, international nurses are faced with challenges that may result in poor integration with their host countries. Methods: Using Cooper's five stages for integrative research reviews, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 52 publications
4
70
0
1
Order By: Relevance
“…), and this is referred to by Kingma () as a gradual deskilling process. Deskilling has been experienced by migrant nurses who worked as professional nurses (Alexis & Shillingford ; Pung & Goh ) or as lower‐skilled health workers (Salami et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…), and this is referred to by Kingma () as a gradual deskilling process. Deskilling has been experienced by migrant nurses who worked as professional nurses (Alexis & Shillingford ; Pung & Goh ) or as lower‐skilled health workers (Salami et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…[28] Pung and Goh mentioned that migrant nurses felt demeaned when communicating on the phone due to their lack of confidence in their speaking ability. [30] This can lead not only to stress but also self-doubt in migrant nurses' own abilities. [31]…”
Section: Communicationmentioning
confidence: 99%
“…[33] Pung and Goh attributed this "culture shock" to the absence of familiar cultural signs such as religion. [30] Although spirituality is often associated with religion, the WHO stated that spiritual care, including giving comfort and physical touch, is essential for all patients. [34] Kaddourah et al suggested that migrant nurses' flexibility and understanding while dealing with challenging religious situations is an important aspect of achieving cultural competence.…”
Section: Religion and Spiritualitymentioning
confidence: 99%
“…In pharmacy in Great Britain (GB – England, Scotland and Wales), the proportion of internationally trained pharmacists (ITPs) has risen from 10.1% in 2004 to 11.8% in 2011 . While a great deal of research has been undertaken on internationally trained doctors (ITDs) and nurses (ITNs), less is known about ITPs . It is known that internationally trained healthcare professionals, including pharmacists, face numerous challenges in their adaptation process into the host heal the care system .…”
Section: Introductionmentioning
confidence: 99%
“…[7] While a great deal of research has been undertaken on internationally trained doctors (ITDs) and nurses (ITNs), less is known about ITPs. [9][10][11][12][13][14][15][16][17][18] It is known that internationally trained healthcare professionals, including pharmacists, face numerous challenges in their adaptation process into the host heal the care system. [10][11][12][13][14][15][16][17][18] Where English is a foreign language, the literature on ITNs and ITDs has identified language and communication barriers as a root cause for issues related to adaptation and integration of these healthcare professionals into the workforce, with some studies raising the potential impact of communication problems on patient safety and quality of care.…”
Section: Introductionmentioning
confidence: 99%